IDX BUMN20 PERFORMANCE MEASUREMENT WITH SHARPE, TREYNOR, AND SORTINO (JEM17: Jurnal Ekonomi Manajemen, 2022)
Portfolio asset management must minimize risk exposure for the investor. Measuring the performance of any asset instrument can be done by looking at risk-reward. Observe stock performance listed in BUMN 20 Index with measurement analytical tools like Sharpe ratio, Treynor Ratio, and Sortino ratio. This study is descriptive quantitative research as this study aims to explain how stock performance measurement with the analytical ratio between 2018 and 2021. All population of this study focuses on IDX BUMN20 constituents. This study uses purposive sampling with criteria. This study reveals that the constituents in IDX BUMN20 with the use of three produce performance dominated by negative values so that they have not been able to exceed the performance of the BI rate as a risk-free investment instrument. This study helps investors make more accurate considerations in making decisions in investing. Keywords : Sharpe ratio, Treynor ratio, Sortino Ratio, IDX BUMN20